The Moderating Role of Islamic Values on Impulse Buying in E-Commerce Promotions: Case of Muslim Students in Semarang - Rezky, Muhammad Rezky; Kafabih, An’im Kafabih (Faculty of Economics and Management, 2025)
The surge in e-commerce in Indonesia has intensified business competition, leading to aggressive promotional strategies that often trigger impulse buying, a behavior misaligned with Islamic teachings on balanced consumption. This study examines the impact of promotions on impulse buying behavior among Muslim students in Semarang and how self-control, taqwa, and sadaqah moderate this relationship. Employing a quantitative approach with SEM-PLS on 100 respondents, this study found that while promotions significantly induce impulse buying, only sadaqah effectively moderates this effect negatively. This suggests that charitable giving can counteract the allure of promotional offers. This study also highlights taqwa and self-control among students as the main issues they face, as those variables are insignificant. Practically, this study advises marketers on ethical promotion strategies and empowers consumers to practice mindful spending. Future studies should consider broader socio-cultural factors and diverse samples to validate these findings and explore the dynamics of these relationships over time.